Development of Class III Student Reading Module Based on Local Wisdom - Nurmadiniati (Education Generation Journal, 2024)
This study aims to produce a reading module based on local wisdom for third grade elementary school students. In this study using research development methods (Research and Development) or R&D with the Four-D (4D) model. The data analysis technique used the calculation of the percentage score of the questionnaire. The questionnaire used was a product validation questionnaire and a student response questionnaire. Based on the results by the expert validators, the results were 92.5% in a very valid category. The results obtained from student responses were 97.25% in the very good category. Therefore, it can be concluded that the reading module for class III students based on local wisdom developed by researchers is valid for students to study independently and get to know local wisdom around them